2014
DOI: 10.2147/opth.s59982
|View full text |Cite
|
Sign up to set email alerts
|

Transformational change: nurses substituting for ophthalmologists for intravitreal injections – a quality-improvement report

Abstract: BackgroundThe dramatic increase in need for anti-vascular endothelial growth factor (anti-VEGF) intravitreal therapy in the treatment of retinal disease and the absence of an equivalent increase in ophthalmologists to undertake such intravitreal injections created a patient-safety risk. Timing of intravitreal therapy (IVT) is critical to prevent vision loss and local clinics lacked capacity to treat patients appropriately. We aimed to improve capacity for IVT by nurse injections.Materials and methodsA multidis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…For instance, re-allocating administration of intra-vitreal injections from physicians to nurses was shown to be a resource-efficient usage of personnel that enabled hospitals to cope with an increase in physicians’ workload. DaCosta and colleagues [ 46 ] together with Michelotti and colleagues [ 47 ] suggested that skill mix (changing professional roles) [ 48 ] is beneficial, acceptable to patients, and an effective use of resources. The effectiveness of skill mix across professions remains relatively unexplored [ 49 ] and the likely consequences of skill mix change need to be explored [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, re-allocating administration of intra-vitreal injections from physicians to nurses was shown to be a resource-efficient usage of personnel that enabled hospitals to cope with an increase in physicians’ workload. DaCosta and colleagues [ 46 ] together with Michelotti and colleagues [ 47 ] suggested that skill mix (changing professional roles) [ 48 ] is beneficial, acceptable to patients, and an effective use of resources. The effectiveness of skill mix across professions remains relatively unexplored [ 49 ] and the likely consequences of skill mix change need to be explored [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…To extrapolate, the favorable safety profile of this device even when used by novices implies its potential to be deployed as an assistive device to facilitate the administration of intravitreal injections by trained vitreoretinal nurses, further reducing the injection burden on doctors. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Nurse injectors have been demonstrated to be able to provide a safe and effective injection service that is well received by patients. 9,19 Costs to the NHS and drug label status were of the least importance to patients and this has potential important consequences to the way off-label drugs are used. There is much in the recent literature debating the use of off-label anti-VEGF agents due to their significant cost saving.…”
Section: Discussionmentioning
confidence: 99%